Representations of Banjar ethnicity and religious identity in Anang Ardiansyah's song lyrics: A Paul Ricoeur hermeneutic approach - Subroto, Wisnu; Nurdin, Encep Syarief; Subiyakto, Bambang; Milyartini, Rita (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
Regional songs serve as repositories of cultural values and identity markers, yet limited scholarly attention has examined their role in transmitting religious and social values within specific ethnic communities. This study applies Paul Ricoeur's three-stage hermeneutic framework—explanation, understanding, and appropriation—to analyze four purposively selected songs by Anang Ardiansyah: Batasmiyah, Bismillah Kata Bamula, Puhun Rambai, and Paris Barantai. Selection criteria included: (1) representation of different thematic elements (religious practice, cultural identity, social solidarity, environmental connection), (2) widespread recognition within Banjar communities, and (3) availability of complete lyrical texts. The explanation stage involved literal textual analysis, understanding examined cultural-contextual meanings within Banjar Islamic traditions, and appropriation explored contemporary relevance for cultural preservation. Analysis reveals three primary symbolic domains: (1) religious integration through ritual terminology (